The Effect of the Number of Nodes on Data Communication Performance in Nomad Clusters Using the Gossip Protocol - Hadikusuma, Ridwan Satrio; Mahyastuty, Veronica Windha; Lukas; Epril Moh Rizaludin (JOIN (Jurnal Online Informatika), 2024)
This research aims to understand the effect of the number of nodes on the performance of data communication in Nomad clusters using the gossip protocol. Through a series of tests, it can be concluded that data communication performance is greatly affected by the number of nodes in the cluster. Tests were conducted using two clusters, where one cluster consists of three nodes. The results show that when using a cluster with three nodes, no packet loss occurs in all data transmissions performed, indicating a reliable communication system. The average latency in one data communication cycle varied in each test, but generally remained within the acceptable range of below 100ms based on data communication quality of service parameters. CPU and disc usage remained relatively stable throughout the experiment. Although there were slight differences in throughput between clusters, the throughput generally remained above 100 Mbps, which is still in the good category according to the research parameters. These results show the importance of taking into account the number of nodes in the cluster in designing and managing data communication systems in a Nomad cluster environment with the gossip protocol.